Presence of Myxoma Virus and Rabbit Hemorrhagic Disease Virus in Sylvilagus andinus in the Antisana Hydrological Conservation Area - Guzmán Arias, Cristian Aymar (2021)
Sylvilagus andinus (Andean rabbit) is one of the native mammal species most commonly seen in the Antisana Hydrological Conservation Area, east of Quito, Ecuador, and its population influences the ecological stability of the Andean moorlands. Its importance rests on being an important link in the food chain and its role in maintaining an intact vegetation and thus hydrological cycle. For this reason, the study of factors that can affect its population size, such as viruses, is important for keeping the ecological balance in the Antisana Hydrological Conservation Area, which is under management for ecological restoration. Two of the most important viruses that affect rabbits are the Myxoma virus (MYXV) and Rabbit hemorrhagic disease virus (RHDV), which causes the fatal diseases Myxomatosis and Rabbit hemorrhagic disease, respectively, in domestic and wild rabbits of the genus Oryctolagus. However, the presence of these viruses in Sylvilagus spp. has been poorly studied and they have not been documented in Sylvilagus andinus. In this study, we used a conventional polymerase chain reaction assay (PCR) to detect the presence of MYXV through the M000.5L/R gene and a reverse transcription polymerase chain reaction assay (RT-PCR) to identify the presence of RHDV through the VP60 gene, on samples obtained from wild rabbits captured in the Antisana Hydrological Conservation Area. The amplicons were sequenced to confirm the presence of Myxoma virus and Rabbit hemorrhagic disease virus in Sylvilagus andinus. The presence of Myxomatosis and Rabbit hemorrhagic disease suggests that these diseases might affect the population dynamics of the Andean rabbit and also reveals the possibility that domestic rabbits in and near the paramo highlands may harbor them.